Searching for Nelly Kaplan - Dupont, Joan (Film Quarterly, 2018)
Critic Joan Dupont went in search of filmmaker Nelly Kaplan, whom she had met at an awards ceremony in Paris over a decade ago. She was famous for one film, La Fiancée du Pirate (A Very Curious Girl, 1969), which had taken France and the international world of women's film festivals by storm. She had slipped out of sight; nobody seemed to know where she was or why. At the Cinémathèque Française, there was only a kind of embarrassment when her name was mentioned and no plan to show her films. This past year has seen a resurgence of interest in the work of Kaplan, and the restoration and rerelease of some of her work by Lobster Films. Dupont met with Kaplan at her Paris apartment to discuss past, present, and future.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUyNS9mcS4yMDE4LjcxLjQuMjI